Experimental Approaches of NMR Spectroscopy Methodology and Application to Life Science and Materials Science - The Nuclear Magnetic Resonance Society of Japan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book describes the advanced developments in methodology and applications of NMR spectroscopy to life science and materials science. Experts who are leaders in the development of new methods and applications of life and material sciences have contributed an exciting range of topics that cover recent advances in structural determination of biological and material molecules, dynamic aspects of biological and material molecules, and development of novel NMR techniques, including resolution and sensitivity enhancement. First, this book particularly emphasizes the experimental details for new researchers to use NMR spectroscopy and pick up the potentials of NMR spectroscopy. Second, the book is designed for those who are involved in either developing the technique or expanding the NMR application fields by applying them to specific samples. Third, the Nuclear Magnetic Resonance Society of Japan has organized this book not only for NMR members of Japan but also for readers worldwide whoare interested in using NMR spectroscopy extensively. .
Protein studies by high pressure NMR -- Isotope-Aided Methods for Biological NMR Spectroscopy: Past, Present and Future -- Advances in NMR data acquisition and processing for protein structure determination -- Advances in high field DNP methods -- Photoirradiation and Microwave irradiation NMR Spectroscopy -- Solid-state NMR under ultrafast MAS rate of 40 - 120 kHz -- Elucidating Functional Dynamics by R1ρ and R2 Relaxation Dispersion NMR Spectroscopy -- Structural Study of Proteins by Paramagnetic Lanthanide Probe Methods -- Structure determination of membrane peptides and proteins by solid-state NMR -- NMR studies on silk materials -- NMR studies on polymer materials -- Solid-State 2H NMR studies of molecular motion in functional materials -- NMR Spectral Observations of the Gases in Polymer Materials -- NMR studies on natural product: Stereochemical determination and conformational analysis in solution and in membrane -- Technical basis for nuclear magnetic resonance approach for glycoproteins.-NMR studies on RNA -- NMR analysis of molecular complexity -- NMR of paramagnetic compounds -- NMR of quadrupole nuclei in organic compounds -- NMR of quadrupole nuclei, inorganic materials -- Protein ligand interactions as studied by NMR -- Protein structure and dynamics determination by residual anisotropic spin interactions.
Keywords: Spectrum analysis; Biochemistry; Optical materials; Materials -- Analysis; Polymers; Spectroscopy; Biochemistry; Optical Materials; Characterization and Analytical Technique; Polymers